Root exudates influence chemotaxis and colonization of diverse plant growth promoting rhizobacteria in the pigeon pea – maize intercropping system - Vora, Siddhi M.; Joshi, Purvi; Belwalkar, Mugdha; Archana, G. (Rhizosphere, 2021)
Intercropping, the co-cultivation of two or more plant species in the same field, has several advantages over growing only one plant species, however, the role of plant-microbe interactions in such a setup is poorly understood. To investigate the influence of rhizosphere colonization by plant growth-promoting rhizobacteria (PGPR) in an intercropping system, a model legume-cereal intercropping system involving maize (Zea mays) and pigeon pea (Cajanus cajan) was assessed for colonization using three different bacterial strains Enterobacter sp. C1D, Pseudomonas sp. G22, Rhizobium sp. IC3109. Cross colonization experiments suggested bacterial movement from one plant species to another in the presence/absence of a mesh barrier, implicating the role of intercrop root exudates. In vitro assays and plant inoculation studies displayed that Enterobacter sp. C1D had a preference for monocropped plants while Rhizobium sp. IC3109 to intercropped plants and Pseudomonas sp. G22 was evenly colonized in both conditions. Organic acids like fumarate, malate, and succinate, as analyzed by LC/MS/MS (MRM), were found to be prominent in monocropped plant root exudates, while co-cultivation resulted in a decrease of the exudation of these metabolites. The PGPR strains showed differential behavioral responses in terms of chemotaxis and biofilm formation towards root exudates of intercropped and monocropped plants. Overall, our study provides pieces of evidence that co-cultivation of legume and cereal plants leads to the variation in root exudates and the response of plant beneficial bacteria. •Rhizobacterial strains promoted growth of C. cajan and Z. mays plants through PGP traits like indole –acetic acid production.•Each strain colonized distinctly in C. cajan – Z. mays intercropping and could cross colonize from one plant to another.•Each strain’s chemotaxis preference to monocropped or intercropped root exudates was different.•Of the root exudate organic acids, only fumarate strongly induced chemotaxis and biofilm production in Rhizobium IC3109.